Inhibition of EZH2 induces NK cell-mediated differentiation and death in invasive bladder cancer - Ramakrishnan, Swathi (2019)
Lysine-specific demethylase 6A (KDM6A) and members of the Switch/Sucrose Non-Fermentable (SWI/SNF) family are known to counteract the activity of Enhancer of Zeste Homolog 2 (EZH2), which is often overexpressed and is associated with poor prognosis in muscle-invasive bladder cancer. Here we provide evidence that alterations in chromatin modifying enzymes, including KDM6A and members of the SWI/SNF complex, are frequent in muscle-invasive bladder cancer. We exploit the loss of function mutations in KDM6A and SWI/SNF complex to make bladder cancer cells susceptible to EZH2-based epigenetic therapy that activates an immune response to drive tumor cell differentiation and death. We reveal a novel mechanism of action of EZH2 inhibition, alone and in combination with cisplatin, which induces immune signaling with the largest changes observed in interferon gamma (IFN-γ). This upregulation is a result of activated natural killer (NK) signaling as demonstrated by the increase in NK cell-associated genes MIP-1α, ICAM1, ICAM2, and CD86 in xenografts treated with EZH2 inhibitors. Conversely, EZH2 inhibition results in decreased expression of pluripotency markers, ALDH2 and CK5, and increased cell death. Our results reveal a novel sensitivity of muscle-invasive bladder cancer cells with KMD6A and SWI/SNF mutations to EZH2 inhibition alone and in combination with cisplatin. This sensitivity is mediated through increased NK cell-related signaling resulting in tumor cell differentiation and cell death.